THE INFLUENCE OF WORK MOTIVATION, WORKLOAD, AND WORK STRESS ON THE PERFORMANCE OF NURSE FOR COVID-19 PATIENTS - Syamsuriansyah; Hizriansyah; Uswatun Hasanah; Rizal Adi Pratama Putra (Universitas Islam Negeri Alauddin Makassar, 2023)
Health needs are objective, therefore their fulfillment is absolute. Health needs are largely determined by health problems in the community and the form of health services in the community. Health services include medical services, medical support services, and medical rehabilitation and care services. These services are carried out through emergency units, outpatient units, and inpatient units. The purpose of this study was to determine and analyze the effect of work stress, workload and job satisfaction on the performance of health workers in inpatient rooms, as well as what are the benchmarks, solutions for medical personnel in providing health services at Hospital X. There is an influence of workload, work stress and work motivation on the performance of nurses for Covid- 19 patients. The design in this study was cross sectional. The sample of this study amounted to 77 people. The research instrument used a questionnaire and the data analysis used the chi-square test. There is an influence of workload, work stress and work motivation on the performance of nurses for Covid-19 patients. Work motivation is the most influential variable on the performance of nurses for Covid-19 patients at the Hospital X with an Exp (B) = 3,447